Mean reticulocyte volume enhances the utility of red cell mean sphered cell volume in differentiating peripheral blood spherocytes of hereditary spherocytosis from other causes - Sukesh C Nair; Neeraj Arora; Sachin Jain; David Inbakumar; Joy Mammen; Usha Sitaram (Wolters Kluwer Medknow Publications, 2015)
Context: Mean sphered cell volume (MSCV) and mean reticulocyte volume (MRV) are additional reticulocyte parameters generated while processing the blood samples on Beckman coulter LH 755 in the reticulocyte mode using the volume, conductivity and scatter technology. It has been observed that the difference between mean corpuscular volume (MCV) and MSCV is higher in the cases of hereditary spherocytosis (HS) and this difference is increasingly being utilized as a screening tool for spherocytes. In addition now there have been new observations that reticulocyte volume in cases of HS is less as compared to normal reticulocyte. Aims: Our aim was to test the usefulness of reticulocyte parameters like MSCV and MRV in distinguishing cases of HS and autoimmune hemolytic anemia (AIHA). Materials and Methods: This is a retrospective and partly prospective study where peripheral blood ethylenediaminetetraacetic acid samples from cases of HS (n = 57) and AIHA (n = 29) were processed on LH 755 in both the differential and the reticulocyte mode. The data generated were analyzed and compared with data from normal healthy donors (n = 46). Results: Using an algorithm of MCV - MSCV >10 and MRV - MSCV <25, a sensitivity of 84.2% and specificity of 94.7% was observed in cases of HS. Conclusions: With the reticulocyte analysis, we may now have a simple and cheap additional tool for screening of HS.